Performa modal Bank Syariah di tengah pandemi covid-19 - Tri Inda Fadhila Rahma Inda (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2021)
Capital is a very important function in overcoming risks that may occur in the Banking Industry. A bank is said to be healthy if a bank has sufficient capital despite possible risks. To see that a bank is healthy, capital indicators are also the most important measurement, namely through the capital adequacy ratio or Capital Asset Ratio (CAR). Things that can affect the size of the capital adequacy ratio can occur due to internal and external factors. Internal factors originating from the banking industry itself, such as profitability, asset quality, company size and liquidity. Meanwhile, external factors come from outside the company such as the macroeconomic condition of a country. The Covid-19 pandemic is one of the impacts that causes the economic condition of a country to weaken which impacts on investment. So this study aims to see how much the ability of Islamic banks in the midst of the Covid-19 Pandemic which began to occur in Indonesia from February 2020 to the end of 2020. And the factors that influence the capital adequacy ratio's size. The findings of this research show that during the Covid-19 pandemic, Islamic banking was able to show its performance as an ever-growing Islamic financial institution seen from the data on the development of assets and growth in deposits. Islamic banking CAR for the period of 2020 remains at a fairly strong level despite the covid-19 pandemic. Meanwhile, one of the internal factors that influence CAR is Return On Assets (ROA) with a significance value of 0.005.